2023
DOI: 10.1136/bmjment-2022-300621
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-specific effects of counselling for depression compared to cognitive–behavioural therapy

Abstract: BackgroundCognitive–behavioural therapy (CBT) and counselling for depression (CfD) are recommended first-line treatments for depression. While they approach change differently, there is little understanding of the impact those approaches have on change during treatment.ObjectivesThis study aimed to identify whether CBT and CfD target different symptoms and explore the implications of modelling choices when quantifying change during treatment.MethodsSymptom-specific effects of treatment were identified using mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…secondary) effects on specific symptoms via changes first occurring in other symptoms directly influenced by treatments. 42 , 43 This reflects that an understanding of the symptom relationship patterns in a particular patient presents opportunities for personalised treatment. A recent trial investigated this by obtaining the symptom relationship patterns of different individuals with eating disorders through ecological momentary assessments, where clinicians thereafter used this information to match patients to specific evidence-based psychotherapy modules aimed at targeting symptoms with the strongest and highest number of connections to other symptoms in each patient.…”
Section: Discussionmentioning
confidence: 99%
“…secondary) effects on specific symptoms via changes first occurring in other symptoms directly influenced by treatments. 42 , 43 This reflects that an understanding of the symptom relationship patterns in a particular patient presents opportunities for personalised treatment. A recent trial investigated this by obtaining the symptom relationship patterns of different individuals with eating disorders through ecological momentary assessments, where clinicians thereafter used this information to match patients to specific evidence-based psychotherapy modules aimed at targeting symptoms with the strongest and highest number of connections to other symptoms in each patient.…”
Section: Discussionmentioning
confidence: 99%
“…This is because recent studies have found indirect (i.e. secondary) effects on specific symptoms via changes first occurring in other symptoms directly influenced by treatments [46][47][48] . This reflects that an understanding of the symptom relationship patterns in a patient presents opportunities for personalised treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For the primary analysis, the PHQ-2 and the sleep item were used as the ‘sleep’ and ‘depressive symptom’ factors. Recent findings indicate that the second, rather than first, session might be better to use as the baseline when modelling change in symptoms during and pre-post treatment in settings such as those from which data were gathered for this study ( O'Driscoll et al, 2023 ). This is because the first appointment is an assessment, whereas the second session is typically the point at which formal treatment starts.…”
Section: Methodsmentioning
confidence: 99%